Assessing the water quality of Suva foreshore for the establishment of estuary and marine recreational water guidelines in the Fiji Islands - Praneel Pranesh Lal (IWA Publishing, 2021)
The Standards for water quality in Fiji defined in the Environment Management Regulations 2007 only relate to effluent discharge into the environment. Urbanisation is contributing to wastewater contamination in receiving estuary and marine recreational waters, thus requiring specific guidelines. To create a baseline for this, a sampling programme with relevant physico-chemical and biological parameters was implemented at 3 sites along the Suva foreshore, for 8 consecutive months, during low and high tides. Analysis was done in triplicates, using standard methods approved for the examination of water and wastewater. In the absence of relevant Fiji guidelines, the results were compared with ANZECC (2000) guidelines for estuary and marine waters. Low DO levels, high COD, TN, NH3, TP, OP and heavy metal concentrations were measured in all 3 sites. For instance, TN and NH3 concentrations as high as 4.44 ±0.99 mg/L and 2.58 ± 0.89 mg/L respectively were recorded in Wailea river (Site 2). The colony counts for the TC, FC and E. coli were in most cases above the limits. These results confirm that wastewater discharges add to the inherent levels of parameters in receiving water bodies and support the need for specific, robust Fiji standards to better monitor water quality in foreshore areas. HIGHLIGHTS Urbanisation contributes to wastewater contamination in Fiji water bodies.; Development of water quality baseline is a pre-requisite for establishing water quality guidelines for water bodies.; Use of indicator organisms to assess water quality affected by discharge of wastewater.; Use of standard methods to develop baseline and water quality guidelines.; Potential effect of tidal movement on water quality of estuaries.;